The Online PhD Experience: A Qualitative Systematic Review - Melián, Efrem; Reyes, José Israel; Meneses, Julio (International Review of Research in Open and Distributed Learning, 2023)
The online doctoral population is growing steadily worldwide, yet its narratives have not been thoroughly reviewed so far. We conducted a systematic review summarizing online PhD students’ experiences. ERIC, WoS, Scopus, and PsycInfo databases were searched following PRISMA 2020 guidelines and limiting the results to peer-reviewed articles of the last 20 years, yielding 16 studies eligible. A thematic synthesis of the studies showed that online PhD students are generally satisfied with their programs, but isolation, juggling work and family roles, and financial pressures are the main obstacles. The supervisory relationship determines the quality of the experience, whereas a strong sense of community helps students get ahead. Personal factors such as motivation, personality, and skills modulate fit with the PhD. We conclude that pursuing a doctorate online is more isolating than face to face, and students might encounter additional challenges regarding the supervision process and study/life balance. Accordingly, this review might help faculty, program managers, and prospective students better understand online doctorates’ pressing concerns such as poor well-being and high dropout rates.